KrygsheldelWar Heroes LT A.W. BEAUCHAMP-PROCTOR - DIE KLEIN MANNETJIE MET DIE LEEUEMOED - Kroukamp, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
Many millions of words have been written about heroes and many more will be written in the future, but this article about the late Captain Andrew Weatherby Beauchamp-Proctor, VC., 050., MC.(Bar), OFC., is special because he was the only South African among nineteen pilots to win the Victoria Cross during the First World War and this little man of 5 feet 2 inches had the guts of a lion - he was determined and courageous in the air - absolutely fearless.